Formulasi Sediaan Lip cream Ekstrak Etanol Bunga Asoka (Ixora coccinea) sebagai Pewarna Alami: Formulation of Lip cream from Ethanol Extract of Asoka Flower (Ixora coccinea) as a Natural Dye - Chintiya Vera Nanda; Dwi Elfira Kurniati; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Asoka flower (Ixora coccinea) possesses pigments that can be used as natural colorants in decorative cosmetics. The use of natural colorants in decorative cosmetics is still limited and the demand for decorative cosmetics especially lip cream is increasing. This research aims to determine whether ethanol extract of Asoka flowers can be used as an alternative natural colorant in lip cream formulations. This research began with extraction of Asoka flowers using maceration method with 96% ethanol solvent and citric acid. Base was optimized using a single thickener and combination of carnauba wax and candelilla wax. Base was evaluated and formulated with flower extract. The formulation quality was determined through organoleptic, homogeneity, spreadability, adhesion, viscosity, and pH tests. The extraction results yielded a yield of 27,1%. Best base was bases F3, F4, and F5. Formulations using Asoka flower extract with 2%, 4%, and 6% produced sequentially light brown, reddish-brown, and red colors. F3 produces the best color at pH 4.6. The evaluation results include the distinctive aroma of chocolate, semi-solid consistency, homogeneity, spreadability, adhesion, viscosity, and pH that meet the pharmaceutical requirements. In conclusion, ethanol extract from Asoka flowers can be utilized as a natural colorant in lip cream formulations. Keywords: Ixora coccinea, Natural Colorants, Lip cream, Carnauba wax, Candelilla wax Abstrak Bunga asoka (Ixora coccinea) memiliki pigmen warna yang dapat digunakan sebagai pewarna alami pada kosmetik dekoratif. Namun penggunaan pewarna alami pada kosmetik dekoratif masih kurang dan permintaan penggunaan kosmetik dekoratif terutama lip cream semakin meningkat. Penelitian ini bertujuan untuk mengetahui apakah ekstrak etanol bunga asoka dapat digunakan sebagai alternatif pewarna alami pada sediaan lip cream. Penelitian ini diawali dengan ekstraksi bunga asoka dengan metode maserasi dengan pelarut etanol 96% dan asam sitrat. Lalu dilakukan optimasi basis dengan pengental tunggal dan kombinasi berupa carnauba wax dan candelilla wax. Basis dievaluasi dan diformulasikan dengan ekstrak bunga asoka. Kualitas sediaan ditentukan melalui uji organoleptis, uji homogenitas, uji daya sebar, uji daya lekat, uji viskositas dan uji pH. Hasil ekstraksi didapatkan rendemen sebesar 27,1%. Formula basis terbaik yaitu F3, F4, dan F5. Sediaan dengan ekstrak bunga asoka konsentrasi 2%, 4%, dan 6% menghasilkan warna berturut-turut coklat muda, coklat kemerahan, dan merah. F3 menghasilkan warna terbaik dengan pH 4,6. Hasil evaluasi karakteristik fisik seluruh sediaan meliputi aroma khas coklat, konsistensi semipadat, homogen serta memiliki daya sebar, daya lekat, viskositas, dan pH yang memenuhi persyaratan evaluasi sediaan lip cream. Disimpulkan bahwa ekstrak etanol bunga asoka dapat digunakan sebagai pewarna alami pada sediaan lip cream. Kata Kunci: Ixora coccinea, Pewarna Alami, Lip cream, Carnauba wax, Candelilla wax